2021
DOI: 10.1093/europace/euab085
|View full text |Cite
|
Sign up to set email alerts
|

Second-generation laser balloon ablation for the treatment of atrial fibrillation assessed by continuous rhythm monitoring: the LIGHT-AF study

Abstract: Aims Balloon-based technologies have been developed to simplify catheter ablation of atrial fibrillation (AF), to improve the clinical outcome of the procedure and to achieve durable pulmonary vein isolation (PVI). The objective of this study is to evaluate the safety and efficacy of second-generation laser balloon (LB2) ablation in the treatment of AF using a continuous cardiac rhythm monitoring strategy. Atrial tachyarrhythmias (ATas) recurrences were assessed with implantable cardiac monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 30 publications
1
24
2
Order By: Relevance
“…Therefore, a 30%–50% overlap ratio is recommended in point-by-point laser ablation. 6 , 8 , 9 However, because lesion size could depend on both power and total laser energy, 19 30% overlapped point-by-point laser ablation may create conduction gaps on linear lesions depending on laser power or energy. Recently, we reported that 50% overlapped laser ablation enabled a higher rate of first-pass PVI (ie, successful PVI after the initial circular laser ablation) than 25% overlapped laser ablations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a 30%–50% overlap ratio is recommended in point-by-point laser ablation. 6 , 8 , 9 However, because lesion size could depend on both power and total laser energy, 19 30% overlapped point-by-point laser ablation may create conduction gaps on linear lesions depending on laser power or energy. Recently, we reported that 50% overlapped laser ablation enabled a higher rate of first-pass PVI (ie, successful PVI after the initial circular laser ablation) than 25% overlapped laser ablations.…”
Section: Discussionmentioning
confidence: 99%
“…6 , 7 The laser balloon catheter has recently evolved to the latest version, the third-generation laser balloon (LB3) (HeartLight X3; CardioFocus, Marlborough, MA) from the first-generation laser balloon (LB1) (HeartLight; CardioFocus) and second-generation laser balloon (LB2) (HeartLight Excalibur Balloon; CardioFocus). 6 , 7 , 8 , 9 , 10 , 11 LB1 and LB2 are generally point-by-point ablation systems, leading to relatively long procedural times. 6 , 7 , 8 , 9 LB3 is newly equipped with a motorized rotational delivery system (RAPID mode) with high power (13 W or 15 W), resulting in a prominent reduction in procedural time compared with LB1 and LB2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The single-arm study LIGHT-AF demonstrated the safety and efficacy of this procedure with a high freedom from recurrences and a low arrhythmic burden in patients who experienced recurrences. 46 Also, a group of investigators based in Japan developed a novel shockwave catheter ablation system, aiming to surpass the limitations of radiofrequency ablation. [47][48][49] They tested the shockwave system on pigs and found a superiority to radiofrequency in lesion depth, myoendocardial injury, and tissue repair.…”
Section: Sonic Ablation Cathetersmentioning
confidence: 99%
“…In addition, the visually guided laser ballon (VGLB; LB1, HeartLight, CardioFocus, Marlborough, MA, USA) is a new effective technique to achieve pulmonary vein isolation. The single‐arm study LIGHT‐AF demonstrated the safety and efficacy of this procedure with a high freedom from recurrences and a low arrhythmic burden in patients who experienced recurrences 46 . Also, a group of investigators based in Japan developed a novel shockwave catheter ablation system, aiming to surpass the limitations of radiofrequency ablation 47–49 .…”
Section: Potential Use Of Ssw In Electrophysiologymentioning
confidence: 99%